Sleep habits in native Brazilian Terena children in the state of Mato Grosso do Sul, Brazil Hábitos de dormir da criança indígena Terena no Mato Grosso do Sul - RUBENS REIMÃO; JOSÉ CARLOS ROSA PIRES DE SOUZA; MARIZÉLIA MAZZINI MEDEIROS; RAQUEL ICASSATI ALMIRÃO (Arquivos de Neuro-Psiquiatria)
Sleep habits in childhood vary in function of physiologcal factors.Cultural traits also influence sleep habits. This research evaluates sleep habits of Native Brazilian Terena children. The Terena group here studied live in the central region of Mato Grosso do Sul, Brazil, on the plains; they are peaceful and dedicated mainly to agriculture. Two villages were studied, Tereré and Córrego do Meio, both in Reservations. Sleep characteristics of 67 children (40M;27F), 2 to 10 year olds, were evaluated in interviews with their mothers. The results evidenced that cosleeping, in the same bed with family members is the standard Terena pattern present in every evaluated child. The presence of two or more beds and a mean of five or more people in each bedroom was the typical finding. The authors propose that cosleeping and the presence of numerous family members reflect the high values attributed to family links in the Terena culture. Os hábitos de dormir variam, na infância, em função de fatores fisiológicos e sofrem influências culturais. O objetivo desta pesquisa foi avaliar os hábitos de dormir da criança indígena Terena, no Mato Grosso do Sul. Duas aldeias foram estudadas, Tereré e Córrego do Meio, ambas em reservas indígenas. As características do sono de 67 crianças (40 M; 27 F), de 2 a 10 anos de idade, foram pesquisadas por meio de entrevistas com as mães. Resultou que o hábito de dormir junto (cosleeping) na mesma cama, com os familiares, foi o padrão mais característico, sendo encontrado em todas as crianças avaliadas. Presença de duas ou mais camas e média de cinco ou mais pessoas no mesmo quarto foram achados típicos. Os autores propõem que dormir junto com familiares, e a presença de numerosos membros da mesma família no mesmo quarto, refletem os valores atribuídos a elos familiares na cultura Terena.